2018
DOI: 10.1155/2018/4135806
|View full text |Cite
|
Sign up to set email alerts
|

Irradiated Human Umbilical Vein Endothelial Cells Undergo Endothelial-Mesenchymal Transition via the Snail/miR-199a-5p Axis to Promote the Differentiation of Fibroblasts into Myofibroblasts

Abstract: Radiation induced pulmonary fibrosis (RIPF) is one of the major side effects of radiotherapy for lung cancer. Previous studies have shown that endothelial cells and activated myofibroblasts play a key role in RIPF. However, the interaction between irradiated endothelial cells and activation of myofibroblasts has not been reported. The aim of the present study was to examine whether irradiated endothelial cells would affect the differentiation of fibroblasts into myofibroblasts in the process of RIPF. In the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 36 publications
2
27
0
1
Order By: Relevance
“…In irradiated human pulmonary artery ECs, EndMT was dependent on HIF-1α expression via TGF-βR1/Smad signaling. Data generated in that study revealed HIF-1α-related EndMT in human RIPF tissues 95 . A recent study provided evidence that in a coculture system of human fetal lung fibroblasts (MRC-5) and irradiated HUVECs, Snail and vimentin expression was upregulated, and CD31 expression was downregulated.…”
Section: Radiation-induced Pulmonary Fibrosis (Ripf)mentioning
confidence: 88%
See 1 more Smart Citation
“…In irradiated human pulmonary artery ECs, EndMT was dependent on HIF-1α expression via TGF-βR1/Smad signaling. Data generated in that study revealed HIF-1α-related EndMT in human RIPF tissues 95 . A recent study provided evidence that in a coculture system of human fetal lung fibroblasts (MRC-5) and irradiated HUVECs, Snail and vimentin expression was upregulated, and CD31 expression was downregulated.…”
Section: Radiation-induced Pulmonary Fibrosis (Ripf)mentioning
confidence: 88%
“…A recent study provided evidence that in a coculture system of human fetal lung fibroblasts (MRC-5) and irradiated HUVECs, Snail and vimentin expression was upregulated, and CD31 expression was downregulated. Radiation-induced EndMT enhances the differentiation of fibroblasts to myofibroblasts via the Snail/ miR-199a-5p axis (Table 2) 95 .…”
Section: Radiation-induced Pulmonary Fibrosis (Ripf)mentioning
confidence: 99%
“…In rhabdomyosarcoma, SNAIL regulates the expression of myogenic-associated miRNAs, such as miR-1, miR-206, and miR-378 [14]. What is more, the SNAIL/miR-199a-5p axis promotes the differentiation of fibroblasts into myofibroblasts by the induction of endothelial-mesenchymal transition [162].…”
Section: Snail Regulation Of Non-coding Rnasmentioning
confidence: 99%
“…Total cell proteins were extracted after treatment with medium (control) and Fn at appointed time. The assays were carried out as previously described 47 . The target proteins were detected with primary antibodies recognizing AKT (Cell Signaling Technology, CST #9272; 1:1,000), p-AKT (CST #4060; 1:2,000), STAT3 (CST #9139; 1:1,000), and p-STAT3 (CST #9145; 1:2,000).…”
Section: Western Blot Assaysmentioning
confidence: 99%